Highly efficient catalysts of ruthenium clusters on Fe3O4/MWCNTs for the hydrogen evolution reaction. (23rd March 2022) - Ramachandra, Shwetha Kolathur; Nagaraju, Doddahalli Hanumantharayudu; Marappa, Shivanna; Kapse, Samadhan; Thapa, Ranjit
Abstract : Anchoring of Ru onto the Fe3 O4 /MWCNTs composite, its HER mechanism and DFT calculated change in Gibbs free energy of adsorbed hydrogen are described. Abstract : Producing molecular hydrogen (H2 ) using water provides a sustainable approach for developing clean energy technologies. Herein, we report highly active ruthenium (Ru) clusters supported on iron oxide (Ru/Fe3 O4 ) and Fe3 O4 /multi-walled carbon nanotubes (Ru/Fe3 O4 /MWCNTs) by simple electrochemical deposition in a neutral aqueous medium. The supported catalyst exhibits good hydrogen evolution reaction (HER) activity in an acidic environment. Cyclic voltammograms (CVs) of potassium ferrocyanide (K4 [Fe(CN)6 ]) confirm that MWCNTs enhance the electron transfer process by decreasing the redox formal potential. The overpotentials of Ru/Fe3 O4 /MWCNTs and Ru/Fe3 O4 electrocatalysts versus the reversible hydrogen electrode (RHE) were found to be 101 mV and 306 mV to reach a current density of 10 mA cm −2 . As prepared, the catalyst displays good stability and retain its HER activity even after 1000 cycles. Furthermore, the stability of Ru/Fe3 O4 /MWCNTs was studied using the chronopotentiometric (CP) technique for 12 h and found negligible loss in the catalytic activity towards the HER. To explore the role of Ru and underneath MWCNTs in improving the catalytic performance of Fe3 O4, density functional theory (DFT) calculations were carried out. DFT calculations indicate that the octahedral site of Ru/Fe3 O4 favors the HER with a low overpotential. However, Ru/Fe3 O4 /MWCNTs are more efficient towards the HER, which could be due to the availability of both octahedral and tetrahedral catalytic sites.